Silencing of SARS‐CoV‐2 with modified siRNA‐peptide dendrimer formulation. Issue 9 (10th May 2021) - Khaitov, Musa; Nikonova, Alexandra; Shilovskiy, Igor; Kozhikhova, Ksenia; Kofiadi, Ilya; Vishnyakova, Lyudmila; Nikolskii, Alexander; Gattinger, Pia; Kovchina, Valeria; Barvinskaia, Ekaterina; Yumashev, Kirill; Smirnov, Valeriy; et al.
Abstract: Background: First vaccines for prevention of Coronavirus disease 2019 (COVID‐19) are becoming available but there is a huge and unmet need for specific forms of treatment. In this study we aimed to evaluate the anti‐SARS‐CoV‐2 effect of siRNA both in vitro and in vivo . Methods: To identify the most effective molecule out of a panel of 15 in silico designed siRNAs, an in vitro screening system based on vectors expressing SARS‐CoV‐2 genes fused with the firefly luciferase reporter gene and SARS‐CoV‐2‐infected cells was used. The most potent siRNA, siR‐7, was modified by Locked nucleic acids (LNAs) to obtain siR‐7‐EM with increased stability and was formulated with the peptide dendrimer KK‐46 for enhancing cellular uptake to allow topical application by inhalation of the final formulation – siR‐7‐EM/KK‐46. Using the Syrian Hamster model for SARS‐CoV‐2 infection the antiviral capacity of siR‐7‐EM/KK‐46 complex was evaluated. Results: We identified the siRNA, siR‐7, targeting SARS‐CoV‐2 RNA‐dependent RNA polymerase (RdRp) as the most efficient siRNA inhibiting viral replication in vitro . Moreover, we showed that LNA‐modification and complexation with the designed peptide dendrimer enhanced the antiviral capacity of siR‐7 in vitro . We demonstrated significant reduction of virus titer and lung inflammation in animals exposed to inhalation of siR‐7‐EM/KK‐46 in vivo . Conclusions: Thus, we developed a therapeutic strategy for COVID‐19 based on inhalation of a modified siRNA‐peptide dendrimer formulation. The developed medication is intended for inhalation treatment of COVID‐19 patients. Abstract : siR‐7, targeting SARS‐CoV‐2 RdRp inhibits viral replication in vitro . LNA‐modification and complexation with peptide dendrimer KK‐46 enhanced the antiviral capacity of siR‐7 in vitro . Inhalation exposure of SARS‐CoV‐2‐infected Syrian Hamsters with siR‐7‐EM/KK‐46 reduces the virus titer and lung inflammation. Abbreviations: GFP, green fluorescent protein; LNA, locked nucleic acid; LUC, luciferase; RISC, RNA‐induced silencing complex; RdRp, RNA‐dependent RNA polymerase; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; siRNA, small interfering RNA; siR‐7‐EM, LNA‐modified small interfering RNA‐7 ​